A multiple case study of teachers' visions and reflective practice. Issue 4 (4th July 2017) - Vaughn, Margaret; Parsons, Seth A.; Keyes, Christopher; Puzio, Kelly; Allen, Melony
Abstract: Researchers have found that teachers' visions of what they hope to instill in their students beyond curricular objectives are integral to their instruction and to larger decisions such as their career paths. The purpose of this research was to examine 10 in-service teachers, who taught in different geographic locations across the United States, their visions, and the ways in which these visions influenced their reflective curricular decisions and instructional actions. The researchers describe salient dimensions of visions, the actions teachers reported to enact visions, and the distance and tensions in enacting visions. Researchers used grounded theory and constant comparative analysis to analyze interviews, questionnaires, and artifacts. Findings explore the relationship between teachers' visions and reflective practice as well as the alignment of instructional practices teachers report in supporting their respective visions. Implications for future research, theory, and practice are discussed.